Enhancing the Efficiency of Animal Feed Production through Digital Marketing and Governance Training - Siahaan, Sabda Dian Nurani; Dede Ruslan; Siti Ulgari; Lenti Susanna Saragih; Dodi Pramana; Saronom Silaban; Eka Putra Dairi Boangmanalu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service aims to enhance and sustain business operations to increase production capacity, ultimately improving the economic conditions of the partners. The process includes analyzing the situation, identifying issues, conducting Focus Group Discussions, preparing tools and materials, providing training and mentoring, and finally, evaluating the outcomes. The community service activity will primarily use training and mentoring methods. Through this, Barisan Sada Orjok members will gain hands-on experience in boosting their business by training and assisting partners with marketplace account creation and e-commerce registration. Additionally, organizational governance training led to the development of a new organizational structure with specific job descriptions for each member.